Initial Training and Teaching Practices as Research Categories in Social Studies - Ramírez Achoy, Jéssica (2020)
The article study on the categories of Initial Teacher Training and Preservice Teachers for research in Social Studies. The interest arises from the research in the Didactics of Social Sciences of the last three decades. For the analysis we use the studies of the 1990s that promoted theoretical models in the Initial Teacher Training and Teaching Practices to understand How to learn teaching.